WORKSHOP DAN KOMPETISI ROBLOX STUDIO DENGAN AI UNTUK SMA/SMK DI JAKARTA DAN SEKITARNYA - Darius Andana Haris; Ivander; Amita Ratu Osswald; Deven Yudino (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
The Roblox Studio Workshop and Competition with AI is a commUnity service activity conducted by the Game Development Lab of the Faculty of Information Technology, Tarumanagara University. The target group of this activity is high school/vocational school students in Jakarta and its surrounding areas. This activity was carried out over two days. The first day was an introduction and training in game Development with an AI approach in Roblox Studio, while the second day was a competition for presentations of work and the determination of winners. In the training session, participants received a basic explanation of Roblox Studio, world design techniques, and how Artificial Intelligence can be applied to support interactions and mechanisms in games. With a hands-on approach, students not only learned theory but also implemented their knowledge in the form of simple projects. For the competition, each team created a metaverse world with the theme